Reduced graphene oxide-supported Ag-loaded Fe-doped TiO2 for the degradation mechanism of methylene blue and its electrochemical properties. Issue 12 (9th February 2018) - Jaihindh, Dhayanantha Prabu; Chen, Ching-Cheng; Fu, Yen-Pei
Abstract : Graphene oxide-based composites have been developed as cheap and effective photocatalysts for dye degradation and water splitting applications. Abstract : Graphene oxide-based composites have been developed as cheap and effective photocatalysts for dye degradation and water splitting applications. Herein, we report reduced graphene oxide (rGO)/Ag/Fe-doped TiO2 that has been successfully prepared using a simple process. The resulting composites were characterized by a wide range of physicochemical techniques. The photocatalytic activities of the composite materials were studied under visible light supplied by a 35 W Xe arc lamp. The rGO/Ag/Fe-doped TiO2 composite demonstrated excellent degradation of methylene blue (MB) in 150 min and 4-nitrophenol (4-NP) in 210 min under visible light irradiation, and trapping experiments were carried out to explain the mechanism of photocatalytic activity. Moreover, electrochemical studies were carried out to demonstrate the oxygen evolution reaction (OER) activity on rGO/Ag/Fe-doped TiO2 in 1 M of H2 SO4 electrolyte, with a scan rate of 50 mV s −1 . The reductions in overpotential are due to the d-orbital splitting in Fe-doped TiO2 and rGO as an electron collector and transporter.